O Haiti é aqui: discussões sobre a cidadania cosmopolita à luz da diáspora haitiana no Brasil - Sara Lucia Moreira de Cerqueira (2018)
2010, particularly in the city of Belo Horizonte and Metropolitan region. The current people flows no longer indicate closed and panned projects, which leads to the conclusion that definitive migration coexists with return and transit migrations. It was observed that the Haitian migration towards Brazil follows such pattern, despite displaying its own characteristics, which contributed to the implementation of important changes in governmental actions and legislation on the subject. The main international legal norms on the protection of the migrant, and, in the national context, the new Law of Migration (Law n. 13.445/2017) were analyzed, with the aim of identifying whether they are sufficient to ensure theses persons the effectiveness of minimal fundamental rights. Beyond the protection of civil rights (individual liberties), this dissertation defends, based on the proposal of Adela Cortina, the protection of political, economic, social and cultural rights of all people on Earth, by means of the universalization of social citizenship, so that we all can identify as citizens of the world, thereby fighting for the minimums of justice demanded by a truly cosmopolitan society.